2017
DOI: 10.1177/0146167217703079
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Active Versus Passive Risks, and the Effect of Personal Responsibility

Abstract: Not getting vaccinated or not backing up computer files are examples of passive risk taking: risk brought on or magnified by inaction. We suggest the difficulty in paying attention to absences, together with the reduced agency and responsibility that is associated with passive choices, leads to the perception of passive risks as being less risky than equivalent active risks. Using scenarios in which risk was taken either actively or passively, we demonstrate that passive risks are judged as less risky than equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…In this case, tolerance “most minimally implying the suspension of certain negative acts against the idea, and involving maximally the active promotion of its circulations” (King, 2012, p. 119). However, psychologically, passivity is less demanding and often less risky and blameworthy than activity (Keinan & Bereby-Meyer, 2017; Kordes-de Vaal, 1996). Thus, people are more likely to engage in passive tolerance rather than active tolerance of disapproved minority practices, but active tolerance does occur.…”
Section: The Dual-process Psychology Of Classical Tolerancementioning
confidence: 99%
“…In this case, tolerance “most minimally implying the suspension of certain negative acts against the idea, and involving maximally the active promotion of its circulations” (King, 2012, p. 119). However, psychologically, passivity is less demanding and often less risky and blameworthy than activity (Keinan & Bereby-Meyer, 2017; Kordes-de Vaal, 1996). Thus, people are more likely to engage in passive tolerance rather than active tolerance of disapproved minority practices, but active tolerance does occur.…”
Section: The Dual-process Psychology Of Classical Tolerancementioning
confidence: 99%
“…ple are more reluctant to forbid something rather than not to permit it (e.g., Janoff-Bulman et al, 2009;Keinan & Bereby-Meyer, 2017;King, 2012). Therefore, in Study 2 participants were randomly assigned to be asked either whether the practice should be forbidden (intolerance)…”
Section: Studymentioning
confidence: 99%
“…This article focuses on active risk-taking behaviour, where individuals remove themselves from areas of safety to head into areas posing health risks, and does not investigate passive risk-taking behaviour, such as failure to act, evacuate or engage in other safety-seeking behaviour. This is because there are potentially different motivating factors, rationale and mechanisms involved in these two types of behaviour and research has found that passive risks are associated with a lower risk perception than equivalent active risks [20]. Previous literature has investigated passive risks associated with disasters and relevant methods to protect passive risk, but there is a lack of research into active risk-taking behaviour.…”
Section: Methodsmentioning
confidence: 99%